2.03 Gbps visible light communication system with 64-QAM-OFDM utilizing a single flip-chip blue GaN-LED. Issue 21 (15th December 2019) - Zhou, Zheng; Liu, Lilin; Wang, Gang
ABSTRACT: In this paper, a visible light communication (VLC) system based on a single flip-chip blue GaN light emitting diode (GaN-LED) with a mesa size of 200 × 1000 µm is presented. This device exhibits a -3dB modulation bandwidth of about 60 MHz, significantly higher than that by commercially available blue LEDs with the same mesa size. A demonstration of wireless communication at speeds exceeding 2 Gb/s is successfully achieved by exploiting 64 quadrature amplitude modulation (QAM) and orthogonal frequency division multiplexing (OFDM), which enable the limited modulation bandwidth of the device to be fully used.